Best Practice Management of Multicultural Character Education in Diversity-Based Schools - Fandir, A. (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study discusses best practices in managing multicultural character education in diversity-based schools. The results show that implementing multicultural values into the curriculum, learning activities, and school policies plays a significant role in creating an inclusive, tolerant, and harmonious educational environment. Success factors are supported by educator competence, policies that accommodate diversity, and active participation from the surrounding community. However, several challenges were identified, such as limited teacher training, inconsistency in policy implementation, and lack of public awareness of the importance of diversity values. This study recommends intensive and continuous training for teachers to improve their understanding of managing diversity. In addition, the development of a curriculum that explicitly integrates multicultural values and policies that support an inclusive culture in schools is highly recommended. Community involvement is also an important element in strengthening the implementation of multicultural education. By implementing these strategic steps, multicultural character education is expected to be an effective solution in building tolerance, cooperation, and social cohesion in a pluralistic society.